The Economic Consequences of Perk Disclosure - Grinstein, Yaniv; Weinbaum, David; Yehuda, Nir (Contemporary Accounting Research, 2017)
Abstract In December 2006, the SEC issued new rules requiring enhanced disclosure by public U.S. firms of perquisites granted to their executives. The rules applied to perquisites granted in fiscal year 2006 and thereafter. Because the rules were implemented quickly, the perks disclosed for 2006 reflect the arrangements firms made under prior disclosure rules: firms could not revise perks to reflect the new rules until 2007. For firms that disclose for the first time in 2006, we predict and find that perks decrease in 2007, reflecting both the costs of increased disclosure and enhanced monitoring. This decrease in perks is offset by higher levels of non‐perk compensation, however. We also predict and find that the effect of perk disclosure by formerly non‐disclosing firms in 2006 leads to higher perks in 2007 for firms that were disclosing perks prior to the rule change.